Erhöht die Riester-Förderung die Sparneigung von Geringverdienern? - Giacomo Corneo; Matthias Keese; Carsten Schröder (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2007)
In 2001 the German government started to promote the development of private pensions by means of special saving subsidies and tax incentives (Riester-scheme). That policy especially targets households with relatively low incomes. Using data from the German Socio-economic Panel, we scrutinize the impact of the Riester-scheme on private saving. Our estimation results suggest that the Riester-scheme neither increases the fraction of households with positive savings, nor increases the households' saving rate. Thus, rather than creating saving, this policy seems to make people substitute previous contracts by subsidized saving contracts.
Keywords: D12; D14; H24; H31; I38; 330; Private Rentenversicherung; Sparförderung; Niedrigeinkommen; Sparen; Deutschland